Studies Vacuum and Nonvacuum Packaging on the Quality of Hump Banana Nugget (Musa acuminate L.) fortified with Fish Protein Concentrate (Pangasius hypopthalmus) - Harahap, Oktavia Iswari; Buchari, Dewita; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The objective of this research was to compare the vacuum packaging and nonvakum on quality of hump banana nugget (Musa acuminate L.) fortified with fish protein concentrate (Pangasius hypopthalmus). Parameter used were sensory evaluation, including appearance, taste, texture and odor by giving the score sheet 25 somewhat trained panelists; the content of water, fat, protein, peroxide value and total colony of bacteria, Which were observed periodically at 0, 10, 20 and 30 days. Result showed that the hump banana nugget fortified with fish protein concentrate stored in vacuum packaging was showing as the best quality, it was indicated for the highest sensory value appearance 8.55-4.71%, odor 8.42-4.63 %, texture 8.50-4.54 % and taste 8.46-4.41 %. The product contained moisture 54.19-62.05 %, fat 3.45-1.49 %, protein 12.04-7.06 %, peroxide value 0.00-7.41 meq/1000 g sample and total colony of bacteria 4,4x103 to 2,2x104 cell/g. The nuggets can be stored for 20 days in cold temperature (± 50C).Keywords: Nugget, packaging, vacuum-nonvacuum